Value creation for sustainability transitions: reframing the impacts of firms on sociotechnical transitions - Venter, Karen Hesse (Stellenbosch : Stellenbosch University, 2025)
Venter, K. H. 2025. Value Creation for Sustainability Transitions: Reframing the Impacts of Firms on Sociotechnical Transitions. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/dbceb74a-8237-4eb7-b0fa-84de90aa28d9